1996
DOI: 10.1007/bf00301021
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric depressed skull fractures: analysis of 530 cases

Abstract: Depressed skull fractures (DSFs) account for 7-10% of children admitted to hospital with a head injury and 15-25% of children with skull fractures. We reviewed the records of 530 patients operated on for DSF from January 1, 1973, to December 31, 1993. This group was made up of 357 boys (67%) and 173 girls (33%) whose ages ranged from 1 day to 16 years (mean age 6.1 years). Fall was the most common cause of injury. Of the 530 patients with DSF, 66% had compound fractures. The incidence of compound fractures inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 13 publications
3
33
0
4
Order By: Relevance
“…In their large series on surgical management of depressed skull fractures in children, Erşahin et al found falls and traffic accidents to be the most common causes of injury. 3 In our study, although a fall was the most common injury in patients overall, those who most frequently had their fracture repaired were hit in the head by an object, and patients who required treatment for their trauma were mostly involved in an MVC. High-impact injuries cause more force to the brain, so it is not surprising that these mechanisms, like MVC, lead to more traumatic injuries.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In their large series on surgical management of depressed skull fractures in children, Erşahin et al found falls and traffic accidents to be the most common causes of injury. 3 In our study, although a fall was the most common injury in patients overall, those who most frequently had their fracture repaired were hit in the head by an object, and patients who required treatment for their trauma were mostly involved in an MVC. High-impact injuries cause more force to the brain, so it is not surprising that these mechanisms, like MVC, lead to more traumatic injuries.…”
Section: Discussionmentioning
confidence: 63%
“…As in our series, there is a male predominance in most reports on skull fracture. 1,3,9,10,16 The most common cause of injury varies among reports, but mainly lists MVCs, 1,10,15 falls, 3,9,13 and assaults 16 as the predominant mechanisms. However, many of these studies do not differentiate between the age of the patients or those who received surgical treatment for the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The most common MOI in our study was falls, which has been noted as a predominant cause of skull fractures in previous publications. 3,4,10 In…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 4-13% of brain abscesses in children are a result of cranial injuries. 19,28,108 For example, many children have sustained penetrating ocular injuries as a result of experimenting with sharp objects such as pencils and sticks, and intracranial extension may lead to an abscess. 4,32,43 The incidence of brain abscesses secondary to penetrating cranial injuries in children has been reported to range from 4.8 to 16%.…”
mentioning
confidence: 99%